Development, evaluation and testing of green organic biofertilizer on promoting horticultural plant growth and soil properties - Nur Alwanie, Maruji (Universiti Malaysia Sarawak (UNIMAS), 2015)
Oil palm’s empty fruit bunches (EFB) are waste products of oil palm industries. Sustainable waste management system promotes the recycling EFB as composting materials. EFB has the potential as compost since it is natural organic material and rich in plant nutrients. Two species of effective microbes which are Bulkholderia unamae P10 and Enterobacter cloacae P11 were used in this study as inoculants to develop biofertilizers. The developed biofertilizers were tested to evaluate the use and application of biofertilizer in promoting the growth of horticultural plant. In this study, Hibiscus rosa-sinensis L. was selected for planting. In-planta induction experiments were conducted to determine whether bacterial inoculant can induce the plant growth in Luria Bertani broth. Overall, the study revealed that there is no apparent difference on plant growth in between the treatments conducted. However, there are no negative impacts on the growth of plants from the application of biofertilizers. Soil properties were studied and it revealed that the application of biofertilizer has improved the soil quality in terms of pH, electrical conductivity and available phosphorus. The result from soil analysis showed that T2 treatment (Bulkholderia unamae P10) can be compared to that of the control treatment which indicates that the T2 compost can improve the quality of the soil.